(untitled) (Revista de Estudos da Linguagem, 2005)
A Portuguese-Tupi dictionary prepared in Belem in 1771 is analysedin the context of the linguistic policy of Pombal’s government inAmazonia, and is compared to Tupi vocabularies compiled in theJesuit period. By these two means, we will examine whether theJesuits continued to serve as a reference during the Pombal periodfor the evangelisation policy in the colony and for the descriptivemodel of Tupi.